2013
DOI: 10.1016/j.amepre.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Control Program Grantees’ Use of Evidence-Based Interventions

Abstract: Background Colorectal cancer (CRC) screening is recommended for adults aged 50–75 years, yet screening rates are low, especially among the uninsured. The CDC initiated the Colorectal Cancer Control Program (CRCCP) in 2009 with the goal of increasing CRC screening rates to 80% by 2014. A total of 29 grantees (states and tribal organizations) receive CRCCP funding to (1) screen uninsured adults and (2) promote CRC screening at the population level. Purpose CRCCP encourages grantees to use one or more of five e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 13 publications
(11 reference statements)
0
44
0
1
Order By: Relevance
“…A previous study assessing the use of Community Guide-recommended EBAs by Colorectal Cancer Control Program Grantees indicated that clinics implemented 3.15 EBAs on average (Hannon et al, 2013). In addition, small media and client reminders were the most commonly used EBAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study assessing the use of Community Guide-recommended EBAs by Colorectal Cancer Control Program Grantees indicated that clinics implemented 3.15 EBAs on average (Hannon et al, 2013). In addition, small media and client reminders were the most commonly used EBAs.…”
Section: Discussionmentioning
confidence: 99%
“…was collected from respondents since they were answering on behalf of clinics. Implementation levels of each CRCS EBA were measured using six different questions (Table 2) (Hannon et al, 2013). The survey also included 12 questions related to clinic characteristics used in analyses (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Investigating these gaps leads to several key findings: 1) practitioners underuse EBIs (91, 92); 2) passive approaches for disseminating EBIs are largely ineffective, because dissemination does not happen spontaneously (15, 121); 3) stakeholder involvement in the research or evaluation process (so-called practice-based evidence that responds to the “pull” of practitioners) is likely to enhance dissemination (80, 81, 85, 88, 97, 99, 180); 4) theory and planning frameworks are useful to guide the uptake of EBIs (172); and 5) capacity-building approaches in health-related settings (public health, medical care, policy) should be time-efficient, consistent with organizational climate, culture and resources, and aligned with the needs and skills of staff members (20, 119). …”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of these interventions found their use resulted in median increases of 11%-15% in completed CRC screenings (14). On average, CRCCP grantees have implemented three EBIs, with client-oriented interventions (i.e., client reminders and small media), which grantees report as easier to implement, being the most commonly used (15). CRCCP grantees were found to be more likely to implement EBIs than state health departments without CDC funding, suggesting that with sufficient programmatic support, these interventions can be widely adopted in various settings and, if implemented, can increase CRC screening (16).…”
Section: Discussionmentioning
confidence: 99%